A virtual dosimetry audit – Towards transferability of gamma index analysis between clinical trial QA groups. Issue 3 (December 2017) - Hussein, Mohammad; Clementel, Enrico; Eaton, David J.; Greer, Peter B.; Haworth, Annette; Ishikura, Satoshi; Kry, Stephen F.; Lehmann, Joerg; Lye, Jessica; Monti, Angelo F.; Nakamura, Mitsuhiro; Hurkmans, Coen; et al.
Abstract: Purpose: Quality assurance (QA) for clinical trials is important. Lack of compliance can affect trial outcome. Clinical trial QA groups have different methods of dose distribution verification and analysis, all with the ultimate aim of ensuring trial compliance. The aim of this study was to gain a better understanding of different processes to inform future dosimetry audit reciprocity. Materials: Six clinical trial QA groups participated. Intensity modulated treatment plans were generated for three different cases. A range of 17 virtual 'measurements' were generated by introducing a variety of simulated perturbations (such as MLC position deviations, dose differences, gantry rotation errors, Gaussian noise) to three different treatment plan cases. Participants were blinded to the 'measured' data details. Each group analysed the datasets using their own gamma index (γ) technique and using standardised parameters for passing criteria, lower dose threshold, γ normalisation and global γ. Results: For the same virtual 'measured' datasets, different results were observed using local techniques. For the standardised γ, differences in the percentage of points passing with γ < 1 were also found, however these differences were less pronounced than for each clinical trial QA group's analysis. These variations may be due to different software implementations of γ. Conclusions: This virtual dosimetry audit has been an informative step in understanding differences in the verification of measured dose distributions between different clinical trial QA groups. This work lays the foundations for audit reciprocity between groups, particularly with more clinical trials being open to international recruitment.